The Complex of Ethidium Bromide with Genomic DNA: Structure Analysis by Polarized Raman Spectroscopy - Tsuboi, Masamichi (Biophysical Society, 2007)
Structural properties of the complex formed between genomic DNA and the intercalating drug ethidium bromide (EtBr) have been determined by use of a Raman microscope equipped with near-infrared laser excitation. The polarized spectra, which were obtained from oriented fibers of the EtBr:DNA complex, are interpreted in terms of the relative orientations of the phenanthridinium ring of EtBr and bases of DNA. Quantification of structure parameters of EtBr and DNA in the complex were assessed using Raman tensors obtained from polarized Raman analyses of oriented specimens of EtBr (single crystal) and DNA (hydrated fiber). We find that the phenanthridinium plane is tilted by 35 ± 5° from the plane perpendicular to the fiber (DNA helix) axis. Assuming coplanarity of the phenanthridinium ring and its immediate base neighbors at the intercalation site, such bases would have a tilt angle closer to that of A-DNA (20°) than to that of B-DNA (6°). The average base tilt in stretches of DNA between intercalation sites remains that of B-DNA.